2019
DOI: 10.3390/microorganisms7120622
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of the Microbiota Composition and Enterotypes of Pigs from Post-Weaning to Finishing

Abstract: The present study aimed at investigating the evolution of pigs’ fecal microbiota composition from post-weaning to finishing in a longitudinal analysis. The experiment was conducted on 160 Pietrain × (Large White × Landrace) castrated male and female pigs in two replicates. Feces were collected at 52, 99, 119, 140, and 154 days of age for further 16S rRNA sequencing to analyze the microbiota composition. Pig microbiota evolved strongly from 52 to 99 days of age with an increased abundance of Streptococcaceae an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 27 publications
5
34
2
Order By: Relevance
“…For humans, geographical or ethnic variations, host genetic, immunity, lifestyle and diet or dietary habits have been reported as factors affecting gut microbiota [21]. Sex [22], genetic performances [23], phase of growth, other than diet [24] have been reported to influence gut microbiota in pigs. In healthy dogs, variations of microbiome with age, from weaning to adulthood, were reported [25,26], with a stabilization of the core gut microbiota at maturity.…”
Section: Discussionmentioning
confidence: 99%
“…For humans, geographical or ethnic variations, host genetic, immunity, lifestyle and diet or dietary habits have been reported as factors affecting gut microbiota [21]. Sex [22], genetic performances [23], phase of growth, other than diet [24] have been reported to influence gut microbiota in pigs. In healthy dogs, variations of microbiome with age, from weaning to adulthood, were reported [25,26], with a stabilization of the core gut microbiota at maturity.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating information about the gastrointestinal tract microorganisms of pigs has been obtained since the extensive application of "omics analysis" (3)(4)(5)(6)(7). It is believed that the gut of neonates is devoid of microbes prior to birth but rapidly undergoes a marked shift from an essentially germ-free state to harboring an extremely dense microbial population that eventually experiences microbial succession and establishes an adult-like microbial community (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…However, gut microbiota varies largely among individuals on time and space scale [ 17 ], which is an obstacle to a better understanding of the complex biological effects of the microbiome. Population stratification is a useful approach to cope with the obstacle, which has found that several equilibrium states—i.e., enterotypes (ETs)—are possible [ 18 ]. The term “enterotype” was first raised by Arumugam et al in 2011, referring to distinct community composition types of human gut microbiota [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ramayo-Caldas et al found that the ET-like clustering was significantly associated with the pig feed efficiency and growth traits, suggesting the ET concept may have an important role in the pig production industry [ 26 , 28 ]. Although relatively robust, ETs are demonstrated to be strongly associated with the pig age, long-term diets, and even different clustering and grouping strategies [ 18 , 28 , 29 , 30 , 31 ]. However, knowledge is also limited to the effects of the different ETs on the butyrate metabolism in pigs.…”
Section: Introductionmentioning
confidence: 99%